XAS study of Mo-based dispersed catalysts for upgrading of heavy oil. (October 2020) - Saraev, A.A.; Zaikina, O.O.; Sosnin, G.A.; Yeletsky, P.M.; Tsapina, A.M.; Zubavichus, Y.V.; Yakovlev, V.A.; Kaichev, V.V.
Abstract: Results of X-ray absorption spectroscopy study of Mo-based dispersed catalysts in the coke residue after catalytic steam cracking, catalytic cracking in the absence of water, and hydrocracking processes are reported. It was found that the catalyst precursor (ammonium heptamolybdate) is transformed to three different forms with the different ratios: MoO3, MoO2, and MoS2 . After the catalytic steam cracking, the catalyst contains mainly MoO2 (∼74%), whereas after hydrocracking, the prevalent form is MoS2 (∼75%). The precursor after water-free catalytic cracking is transformed into 37% MoO2 and 63% MoS2 . The catalyst genesis scheme in the processing of heavy oil was suggested, taking into account that reaction media affect the active phase formation, resulting in different composition and properties of products. Highlights: Mo-based dispersed catalysts accumulated in coke residues were studied by XANES and EXAFS. Ammonium heptamolybdate was transformed to MoO3, MoO2, and MoS2 with different ratios under reaction media. After hydrocracking and catalytic cracking without water, more than 60% of molybdenum was found in the form of MoS2 . After catalytic steam cracking, only 10% of ammonium heptamolybdate was transformed into MoS2 .